2014
DOI: 10.1016/s1995-7645(14)60227-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and incrimination of sandflies (Psychodidae: Phlebotominae) captured in city and suburbs of Hamadan, Hamadan province, west of Iran

Abstract: Although none of the 158 dissected female Phlebotomus kandelaki and Phlebotomus papatasi were infected with leishmania promastigote, it is probable that in the future, factors such as environmental changes, migration and urbanization can ease the transmission of leishmaniases in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
2
7
1
Order By: Relevance
“…The abundance of P. papatasi and absence of P. sergenti in the outskirts of Yazd may also indicate the lower tendency of P. sergenti to rodent burrows or Haloxylon (a plant that has been cultivated for reconditioning of the desert). Similar to other studies [ 6 , 11 ] which used the sticky traps to collect Phlebotominae sand flies male/female sex ratio for most species was more than one, except for P. caucasicus which was less than one. Such differences were also reported in the case of P. duboscqi in Northern Ethiopia [ 17 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The abundance of P. papatasi and absence of P. sergenti in the outskirts of Yazd may also indicate the lower tendency of P. sergenti to rodent burrows or Haloxylon (a plant that has been cultivated for reconditioning of the desert). Similar to other studies [ 6 , 11 ] which used the sticky traps to collect Phlebotominae sand flies male/female sex ratio for most species was more than one, except for P. caucasicus which was less than one. Such differences were also reported in the case of P. duboscqi in Northern Ethiopia [ 17 ].…”
Section: Discussionsupporting
confidence: 76%
“…The result of this study showed that the activity of sand flies in Yazd starts in early-April and ends in mid-November and there were two peaks of activity, one at the end of April and the other in late September. In comparison to some other studies in Iran such as the studies of Salehzadeh et al [ 11 ] and Azizi et al [ 12 ] which were carried out in regions with more temperate climate, one of the most important differences is the long distance between the first and second peaks of Phlebotominae activity in Yazd. Such distance between two activity peaks of sand flies has also been reported in Sistan-Baluchistan Province, Southeast Iran [ 13 ].…”
Section: Discussionmentioning
confidence: 77%
“…The cutaneous form is the common form of the disease and its history in Iran dates back to about one thousand years ago; the age of Avicenna, an Iranian physician (8). There are two forms of CL in the country: anthroponotic cutaneous leishmaniasis (the urban or dry type) and zoonotic cutaneous leishmaniasis (the rural or wet type) which are caused by L. tropica and L. major , respectively (9). Despite basic information on the etiology, vectors, and method of transmission of the disease, CL continues to be a serious health problem in Iran, and in some parts of the country, the number of cases is rising (10).…”
Section: Introductionmentioning
confidence: 99%
“…papatasi and ph. sergenti sandflies as the main vectors of this disease [12]. The main reservoirs of urban form are humans with CL and occasionally dogs; and rural form reservoirs are mainly desert rodents such as Rombomis opimus, Meriones lybicus, and tatera indica [13].…”
Section: Introductionmentioning
confidence: 99%